Some Escape Time Results for General Complex Polynomials and Biomorphs Generation by a New Iteration Process - Lateef Olakunle Jolaoso; Safeer Hussain Khan (Mathematics, 2020)
Biomorphs are graphic objects with very interesting shapes resembling unicellular and microbial organisms such as bacteria. They have applications in different fields like medical science, art, painting, engineering and the textile industry. In this paper, we present for the first time escape criterion results for general complex polynomials containing quadratic, cubic and higher order polynomials. We do so by using a more general iteration method also used for the first time in this field. This also generalizes some previous results. Then, biomorphs are generated using an algorithm whose pseudocode is included. A visualization of the biomorphs for certain polynomials is presented and their graphical behaviour with respect to variation of parameters is examined.